Plastic bodies in a plastic world: multi-disciplinary approaches to study endocrine disrupting chemicals. (1st January 2017) - Vandenberg, Laura N.; Luthi, Derek; Quinerly, D.'Andre
Abstract: In the 1950's and 60's, there was significant development of synthetic materials for use in consumer products. Plastics of all kinds were produced and have since been incorporated into countless materials. Producers of these chemicals and materials have assumed that they would not have effects on humans or wildlife if exposures remained low. Yet evidence from field studies, controlled laboratory animal experiments and epidemiology has challenged this assumption. Many compounds used in plastics have been characterized as endocrine disrupting chemicals (EDCs), chemicals that interfere with the proper functioning of the endocrine system. EDCs present new challenges to both the industries that produce chemicals and manufacture consumer products, as well as the agencies that are tasked to protect public health. This review will address the issue of developmental plasticity – the concept that developing organisms can adapt to various environmental insults to allow the individual to survive. Studies of EDCs have revealed that developing organisms have tremendous capacity to adapt, but not without significant costs to the individual. We will also address recent efforts by environmental health scientists and green chemists to work collaboratively to solve some of the biggest problems in the field of endocrine disruption. We argue that the use of 21st Century tools and sustainability frameworks will help to avoid 'regrettable replacements' and provide society with workable solutions to the issue of endocrine disruption. Further, we conclude that a truly sustainable future demands that exposures to EDCs should be eliminated whenever possible.